2019
DOI: 10.1016/j.foodres.2019.108528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different ageing methods on colour, yield, oxidation and sensory qualities of Australian beef loins consumed in Australia and Japan

Abstract: Effects of different ageing methods on colour, yield, oxidation and sensory qualities of Australian beef loins consumed in Australia and Japan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 34 publications
4
42
1
4
Order By: Relevance
“…The 10 tastings for each sample were averaged to give the final eating quality score for each. The methodology for sample collection, allocation to treatments, allocation to consumer sessions, cooking, running of consumer sessions, analysis of the line scales, and averaging were first described in Watson, Gee, Polkinghorne and Porter [34], and have been used in consumer research on beef [32,33,35], pork [28] and lamb [27] in Australia and in many countries including Japan [36], South Africa [37] and Korea [38].…”
Section: Methodsmentioning
confidence: 99%
“…The 10 tastings for each sample were averaged to give the final eating quality score for each. The methodology for sample collection, allocation to treatments, allocation to consumer sessions, cooking, running of consumer sessions, analysis of the line scales, and averaging were first described in Watson, Gee, Polkinghorne and Porter [34], and have been used in consumer research on beef [32,33,35], pork [28] and lamb [27] in Australia and in many countries including Japan [36], South Africa [37] and Korea [38].…”
Section: Methodsmentioning
confidence: 99%
“…Dry aging is used to enhance meat tenderness and flavor [9,10]. To meet this improvement on sensory quality, how the producers select the meat cuts (raw material) can impact the process and the final quality of the product.…”
Section: Origin and Raw Materials Informationmentioning
confidence: 99%
“…This process is usually termed ‘wet’ ageing. In contrast, ‘dry’ ageing of beef refers to the ageing of unpackaged primals in air under strictly controlled conditions including temperature, moisture, and air velocity [ 3 ]. Dry aged beef is often marketed as a premium product with improved flavour by high-end butchers and restaurants, although it remains controversial whether the sensory quality of dry aged beef is higher than that of wet aged beef [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dry aged beef is often marketed as a premium product with improved flavour by high-end butchers and restaurants, although it remains controversial whether the sensory quality of dry aged beef is higher than that of wet aged beef [ 4 ]. A more recent study showed that dry aged beef received significantly higher overall and flavour liking scores compared to wet aged counterparts using Meat Standard Australia (MSA) consumer panels with 1440 consumers [ 3 ]. Although both ageing methods improve most palatability attributes of beef, wet aged meat was reported to be associated with negative flavours including sour, ‘serumy’, and metallic, whereas the dry ageing is known to enhance the positive flavours, such as nutty, roasted, and buttery, in beef [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation